Improved Cognitive Performance and Reduced Monocyte Activation in Virally Suppressed Chronic HIV After Dual CCR2 and CCR5 Antagonism. (1st September 2018) - D'Antoni, Michelle L.; Paul, Robert H.; Mitchell, Brooks I.; Kohorn, Lindsay; Fischer, Laurent; Lefebvre, Eric; Seyedkazemi, Star; Nakamoto, Beau K.; Walker, Maegen; Kallianpur, Kalpana J.; Ogata-Arakaki, Debra; Ndhlovu, Lishomwa C.; et al.
Abstract : Objective: To evaluate changes in neuropsychological (NP) performance and in plasma and cell surface markers of peripheral monocyte activation/migration after treatment with cenicriviroc (CVC), a dual C-C chemokine receptor type 2 (CCR2) and type 5 (CCR5) antagonist, in treatment-experienced, HIV-infected individuals. Setting: Single-arm, 24-week, open-label clinical trial. Methods: HIV-infected individuals on antiretroviral therapy ≥1 year with plasma HIV RNA ⩽50 copies per milliliter and below-normal cognitive performance [defined as age-, sex-, and education-adjusted NP performance (NPZ) <−0.5 in a single cognitive domain or in global performance] were enrolled. Changes over 24 weeks were assessed for global and domain-specific NPZ scores, plasma markers of monocyte/macrophage activation [neopterin, soluble (s)CD14, and sCD163] quantified by ELISA, and CCR2 and CCR5 expression on monocytes, and T cells measured by flow cytometry. Results: Seventeen of 20 enrolled participants completed the study. Improvements over 24 weeks were observed in global NPZ [median change (Δ) = 0.24; P = 0.008], and in cognitive domains of attention (Δ0.23; P = 0.011) and working memory (Δ0.44; P = 0.017). Plasma levels of sCD163, sCD14 and neopterin decreased significantly ( P 's < 0.01). CCR2 and CCR5 monocyte expression remained unchanged; however, CCR5 levels on CD4 + and CD8 + T cells and CCR2 expression on CD4 + T cells increased ( P 's < 0.01). Conclusions: CVC given over 24 weeks was associated with improved NP test performance and decreased plasma markers of monocyte immune activation in virally suppressed, HIV-infected participants. These data potentially link changes in monocyte activation to cognitive performance. Further study of CVC for HIV cognitive impairment in a randomized controlled study is warranted. Abstract : Supplemental Digital Content is Available in the Text.